723. Epidemiology, Risk Factors, and Treatment Considerations for Pyogenic Liver Abscess (PLA) in the Calgary Health Zone (CHZ) Revisited: A Population-Based Study. (31st December 2020) - Losie, Jennifer A; Parkins, Michael; Lam, John; Gregson, Daniel
Abstract: Background: PLA is a significant cause of morbidity and mortality. However, its epidemiology and outcomes have not been recently evaluated in the CHZ. Understanding current trends will help guide management. Methods: In this population-based study, we evaluated epidemiology, risk factors, and treatment of patients with PLA in the CHZ. CHZ residents aged ≥ 20 years diagnosed with PLA in 2015-2017 were included. Charts were reviewed for demographics and clinical outcomes. Multivariate logistic regression was used to determine factors associated with 30-day mortality. Findings were compared to a previous assessment of PLA in the CHZ from 1999-2003 (Kaplan et al., 2004). Results: A total of 136 patients with PLA were identified, representing an annual incidence rate of 3.7 cases per 100, 000 population. Compared to 1999-2003, incidence of PLA was increased (2.3 per 100, 000; p< 0.01) but mortality was similar (1999-2003: 0.22 per 100, 000 vs. 2015-2017: 0.26 per 100, 000; p=0.6). The most common culprit organisms were Streptococcus anginosus group (40%), Klebsiella species (25%), Escherichia coli (18%), and obligate anaerobes (16%). Pathogen prevalence was similar to the prior cohort. Compared to 1999-2003, antibiotic resistant organisms were more frequent (8% vs 1%, p=0.04). In our cohort, liver aspirations were less frequent (p=0.02) but aspirate culture was more often positive (p< 0.01). The median duration of intravenous antibiotic therapy was longer compared to previous (2015-2017: 23 days (IQR 9-38) vs. 1999-2003: 17 days (IQR 10-29); p=0.001). Similarly, the total duration of antibiotic therapy was longer (2015-2017: 42 days (IQR 25-65) vs. 1999-2003: 31 days (IQR 18-45); p< 0.001). Thirty-day mortality from admission was 7% and did not differ amongst cohorts. Risk factors are shown in Table-1. Table-1: Risk factors for 30-day mortality in PLA Conclusion: Incidence of PLA in the CHZ is rising with more antimicrobial resistance. Diagnostic liver aspirations are less frequent. Antibiotic durations are longer with no reduction in mortality. Understanding changing trends is valuable in directing future care. Encouraging liver aspirations to obtain a microbiologic diagnosis, especially with increasing resistance, is crucial. Considering shorter antibiotic durations in light of stable mortality warrants further exploration. Disclosures: All Authors : No reported disclosures